2012
DOI: 10.1021/jf2045284
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Antioxidant Activities of Essential Oils and Their Constituents from Leaves of the Taiwanese Cinnamomum osmophloeum

Abstract: Cinnamomum osmophloeum Kaneh is an indigenous tree species in Taiwan. In this study, phytochemical characteristics and antioxidant activities of the essential oils and key constituents from the leaves of two C. osmophloeum clones were investigated. The two trees possess two chemotypes, which were classified as the cinnamaldehyde type and camphor type. We demonstrated that the essential oils from C. osmophloeum leaves exerted in vivo antioxidant activities in Caenorhabditis elegans. In addition, trans-cinnamald… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 31 publications
0
39
0
1
Order By: Relevance
“…Previous studies have demonstrated that both extracts and essential oils from C. cassia exhibit antioxidant activity [32,33]. In addition, the essential oil from the related cinnamon species C. osmophloeum and its major constituent, trans -cinnamaldehyde, exerted significant in vivo antioxidant activities against juglone-induced oxidative stress in Caenorhabditis elegans [34]. Therefore, we investigated whether exposure to CC-EO and cinnamaldehyde would reduce the oxidative stress in α-MSH-stimulated cells.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated that both extracts and essential oils from C. cassia exhibit antioxidant activity [32,33]. In addition, the essential oil from the related cinnamon species C. osmophloeum and its major constituent, trans -cinnamaldehyde, exerted significant in vivo antioxidant activities against juglone-induced oxidative stress in Caenorhabditis elegans [34]. Therefore, we investigated whether exposure to CC-EO and cinnamaldehyde would reduce the oxidative stress in α-MSH-stimulated cells.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous study showed that essential oils from leaves of cinnamaldehyde-and camphor-type C. osmophloeum trees exhibited antioxidant activities in C. elegans. 11 To investigate whether essential oils from the leaves of the mixed-type C. osmophloeum tree have protective effects against oxidative stress in C. elegans, wild-type N2 nematodes were pretreated with extracts immediately followed by exposure to juglone-induced oxidative stresses. Wild-type N2 synchronized L1 larvae were pretreated with 0, 1, 5, 10, and 20 μg/mL extracts and 0.1% DMSO as the solvent control for 72 h before being exposed to juglone (250 μM) and then were incubated for 3 h. Juglone was used as the oxidative stress generator because it is a redox-active quinone capable of intracellular redox cycling with superoxide radical O 2…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…is an indigenous tree species in Taiwan. 7 C. osmophloeum contains essential oils showing multiple biological activities, including antibacterial, 8 antifungal, 9 anti-inflammatory, 10 and in vivo antioxidant 11 activities. Other beneficial properties of the essential oils of C. osmophloeum, however, remain further explored.…”
Section: ■ Introductionmentioning
confidence: 99%
“…C. tamala has potential antioxidant activities in diabetic rats [68], while C. osmophloeum , a species from Taiwan, has significant in vitro and in vivo antioxidant activities under oxidative stress [69]. The antioxidant activity of C. zeylanicum has been investigated using various methods.…”
Section: Antioxidant Activitymentioning
confidence: 99%